Kümeleme analizine göre sağlık göstergeleri açısından Avrupa Birliği ülkeleri içinde Türkiye’nin konumu - Erdem, Ceyda (My University, 2017)
Bu çalışmada Türkiye’nin, Avrupa Birliği’ne üye 28 ülke ve 4 aday ülkeiçindeki sağlık durumu, Dünya Sağlık Örgütü (WHO) tarafından belirlenen 6 sağlıkgöstergesi (kaba doğum hızı, kaba ölüm hızı, bebek ölüm hızı, beş yaş altı orantılı ölümhızı, toplam doğurganlık hızı, doğumda beklenen yaşam süresi) dört dönem “1986,1995, 2004, 2013” karşılaştırılarak açıklanmış ve bu konu için Hiyerarşik KümelemeYöntemi olan Ward Yöntemi, Kareli Öklid Uzaklığı esas alınarak uygulanmıştır.Dört dönemin sonuçları karşılaştırılarak, Türkiye’nin hangi ülkeler ilebenzerlik gösterdiği ve konumu belirlenmeye çalışılmıştır. Kümeleme Analizisonucunda elde edilen bulgular her dönem için beş küme oluşturmuştur. Gelişmişülkeler olarak kabul edilen Avusturya, Almanya, İtalya, İspanya, Yunanistan, Portekizve Slovenya’nın birlikte kümelendiğini göstermektedir. Doğu ve Kuzey Avrupa ülkeleriolan Bulgaristan, Macaristan, Litvanya, Letonya da aynı kümede yer almaktadır.1986dönemi hariç, diğer dönemler için Kuzey ve Batı Avrupa ülkeleri Danimarka, İngiltere,Finlandiya, Fransa, Hollanda, İrlanda, Lüksemburg, İsveç birlikte kümelenmiştir.AB’ye aday ülke olarak gösterilen Bosna Hersek, Karadağ, Arnavutluk ve Makedonyaise her dönem için farklı kümelerde yer alarak, benzerlik göstermemişlerdir. Türkiyeise, 1986 ve 2004 dönemlerinde hiçbir kümeye dahil olmadan, tek gözlem olarakkalırken; 1995 ve 2013 dönemlerinde AB’ye aday bir ülke olan Arnavutluk ile birleşipbir küme oluşturmuştur. Türkiye’nin bu durumda, sağlık göstergesi bakımından, AB’yeüye ülkelere yeterince erişemediği görülmüştür.

In this article the medical position of Turkey among the 28 members and 4canditate countries of the European Union has been evidenced by comapring andcontrasting the results of four years of research: “1986, 1995, 2004, 2013”. The researchhas been carried on by utilizing the 6 health indicators (crude birth rate, crude mortalityrate, baby mortality rate, under five years of age mortality rate, total fertility rate, lifeexpectancy at birth) determined by the World Health Organization. This subject hasbeen based on the hierarchical clustering method known as: ward method, the squareeuclidean distance.To which member countries and canditate countries of the EU Turkey sharesimilarities which have been shown by comparing the results of the aforementionedyears. Additionally; Turkey’s position among them has also been outlined. The findingsacquired as a result of the clustering analysis have generated 5 clustering per year. Thefindings indicated that the countries of: Austria, Germany, Italy, Spain, Greece,Portugal, which are acknowledged as developed countries have heaped together andtook place in the same clustering. It also shows that the Eastren and Northren Europeancountries of Bulgaria, Hungary, Lithuania and Latvia have also taken place in the sameclustering. Furthermore, the findings showed that the Westren and Northren Europeancountries of: Denmark, England, Finland, France, The Netherlands, Ireland,Luxembourg and Switzerland have also heaped together in the same clustering in theaforementioned years, save for 1986. Whereas the EU candidate countries of: Bosniaand Herzegovina, Montenegro, Albania, and Macedonia have not shown smilarities bytaking place in different clusterings in the four years. As for Turkey, it has not takenplace in any clustering in the years: 1986 and 2004 whearas on the other hand; hasformed a clustering by joining with the EU canditate country: Albania, in the years 1995and 2013. It clearly shows that Turkey in this situation, is not sufficiently in par with theEU members of countries in terms of health indicator.
Keywords: Araştırma; Avrupa Birliği; Avrupa Birliği ülkeleri; Ekonometri; İstatistik; Kümeleme Analizi; Sağlık göstergeleri; The ClusterAnalysis; The European Community; The Health Indicators; Turkey; Türkiye